Brazilian Symposium on Software Engineering 2021
DOI: 10.1145/3474624.3477073
|View full text |Cite
|
Sign up to set email alerts
|

Towards Improving Experimentation in Software Engineering

Abstract: Background:] Experimentation in Software Engineering plays a central role on sharing and verifying scientific findings. As experiments have increased significantly in Software Engineering area, we observe that most of them fail to provide a way to be repeated, replicated or reproduced, thus jeopardizing or delaying the evolution of the Software Engineering area. [Aims:] In this vision paper, we present and discuss techniques and infrastructure to continuously improve experiments towards repeatability, replicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…As a way of defining the experimental methods, we identified the use of the approach with a certain objective of the study, selecting the variables to be observed and the form of control to be adopted. This information is corroborated in [14].…”
Section: Introductionsupporting
confidence: 63%
“…As a way of defining the experimental methods, we identified the use of the approach with a certain objective of the study, selecting the variables to be observed and the form of control to be adopted. This information is corroborated in [14].…”
Section: Introductionsupporting
confidence: 63%
“…Even with advances observed in the ESE area [OliveiraJr et al 2021], there are still relevant issues to be addressed, such as, improving the level of reproducibility [González-Barahona and Robles 2012, Baker 2016, Anchundia et al 2020, Nelson et al 2021] and lack of sharing of experimental artifacts [Timperley et al 2021, Damasceno et al 2021, which prevent the software engineering evolution as a formal scientific discipline. It is understood that such an ESE evolution might be reached by increasing the formalization of the experiments carried out straightforwardly based on open science practices applied to SE [Mendez et al 2020].…”
Section: Introductionmentioning
confidence: 99%